2019
DOI: 10.4085/1062-6050-374-18
|View full text |Cite
|
Sign up to set email alerts
|

The Prioritized Research Agenda for the Athletic Training Profession: A Report From the Strategic Alliance Research Agenda Task Force

Abstract: Context Athletic trainers (ATs) must be equipped with evidence to inform their clinical practice. A systematic, inclusive, and continuous process for exploring research priorities is vital to the success of ATs and, more importantly, their patients' positive outcomes. Objective To identify research priorities and unify research with clinical practice to improve patient care and advance the profession. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 7 publications
0
33
0
Order By: Relevance
“…16 As the patient's perspective of a medical interaction is fundamental to their likelihood to seek care, we chose to highlight the patient's experiences which directly aligns with the 2019 Research Agenda O n l i n e F i r s t conducted by the National Athletic Trainers' Association Strategic Alliance Research Agenda Task Force which identified athletic trainers need additional research on the extent that PCC is applied to aid in their clinical decision-making. 17 Therefore, the purpose of this study was to examine what collegiate student-athletes believe is PCC, their perception of how well athletic trainers at their institution embody the domains of PCC, and finally measure the patient's perceptions of patient-centeredness during their most recent encounter with an athletic trainer.…”
Section: Introductionmentioning
confidence: 99%
“…16 As the patient's perspective of a medical interaction is fundamental to their likelihood to seek care, we chose to highlight the patient's experiences which directly aligns with the 2019 Research Agenda O n l i n e F i r s t conducted by the National Athletic Trainers' Association Strategic Alliance Research Agenda Task Force which identified athletic trainers need additional research on the extent that PCC is applied to aid in their clinical decision-making. 17 Therefore, the purpose of this study was to examine what collegiate student-athletes believe is PCC, their perception of how well athletic trainers at their institution embody the domains of PCC, and finally measure the patient's perceptions of patient-centeredness during their most recent encounter with an athletic trainer.…”
Section: Introductionmentioning
confidence: 99%
“…3,8,9 Knowing that ATs are using a variety of modes and systems for documentation, it is necessary to understand their documentation practices. Additionally, the recently released ''Prioritized Research Agenda for the Athletic Training Profession'' 10 identified gaining more insight into the documentation practices of ATs as an important goal. Therefore, the purpose of our study was to determine ATs' perceived strategies for and challenges in documenting patient care.…”
mentioning
confidence: 99%
“…25 Standard operating procedures and standardized reporting methods may provide strategies for improving documentation habits. 17,56 In addition, comprehensive and continuous EMR training preserves data quality, 56,57 and documentation peer reviews can hold clinicians accountable for their documentation practices. 57 Thus, these strategies should be used before and during EMR-based research efforts to optimize data quality.…”
Section: Considerationsmentioning
confidence: 99%
“…On a global health care level, electronic records have been used to better understand disease diagnoses and prognoses, 10,11 improve disease treatment and management strategies, 12,13 reduce health care costs, 14,15 and improve patient outcomes. 16 Because of these benefits, members of the Athletic Training Strategic Alliance 17 have encouraged the use of HIT in athletic training, including electronic records. Although the terms electronic medical record (EMR) and electronic health record (EHR) are often used interchangeably, they are different.…”
mentioning
confidence: 99%